2014
DOI: 10.1136/gutjnl-2014-307345
|View full text |Cite
|
Sign up to set email alerts
|

Progressive genomic convergence of twoHelicobacter pyloristrains during mixed infection of a patient with chronic gastritis

Abstract: ObjectiveTo study the detailed nature of genomic microevolution during mixed infection with multiple Helicobacter pylori strains in an individual.DesignWe sampled 18 isolates from a single biopsy from a patient with chronic gastritis and nephritis. Whole-genome sequencing was applied to these isolates, and statistical genetic tools were used to investigate their evolutionary history.ResultsThe genomes fall into two clades, reflecting colonisation of the stomach by two distinct strains, and these lineages have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 50 publications
(58 reference statements)
0
45
0
1
Order By: Relevance
“…For example, while Mycobacterium tuberculosis may accumulate approximately four SNPs per genome per 4 years [4], Helicobacter pylori can exhibit over 30 SNPs per genome per year [5]. Recombination, the exchange of genetic material between bacteria, ranges from rare (M. tuberculosis) [6] to strong enough for large-scale confusion of phylogenetic interrelationships in gene trees (Streptococcus pneumoniae, H. pylori) [7,8]. The causes of variability in genome content are large insertions, deletions, genome rearrangements and transfer of exogenous DNA, and extrachromosomal elements such as plasmids and phages.…”
mentioning
confidence: 99%
“…For example, while Mycobacterium tuberculosis may accumulate approximately four SNPs per genome per 4 years [4], Helicobacter pylori can exhibit over 30 SNPs per genome per year [5]. Recombination, the exchange of genetic material between bacteria, ranges from rare (M. tuberculosis) [6] to strong enough for large-scale confusion of phylogenetic interrelationships in gene trees (Streptococcus pneumoniae, H. pylori) [7,8]. The causes of variability in genome content are large insertions, deletions, genome rearrangements and transfer of exogenous DNA, and extrachromosomal elements such as plasmids and phages.…”
mentioning
confidence: 99%
“…H. pylori is a bacterium that can display very fast local adaptive processes via mutation and recombination (Cao Q et al, 2015;Furuta Y et al, 2015). The phylogenetics, population genetics and protein evolutionary analysis suggest that alpA in Colombia has functionally divergent variants that are the result of gene conversion in a staggeringly short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…11, 2016; from the US. Since it has been shown that H. pylori from the same population (hpEastAsia) can exchange 10% of their genome during a single 4-year mixed infection in human [21], the ancestral pattern in US H. pylori implies barriers to recombination between the two populations. Such barriers may be the result of ethnic segregation and thus less diverse co-infections, of differential uptake or incorporation of DNA from different populations, or of efficient competitive exclusion of bacteria from one population by bacteria from the other within individual stomachs.…”
Section: Discussionmentioning
confidence: 99%